Reutilization of waste tire into concrete-rubber composite - Mokhzani Khair, Ishak; Khairul Nizar, Ismail; Wan Mohd Sabki, Wan Omar; Kamarudin, Hussin; Mohd Asri, Ab. Rahim; Umar, Kassim; Libren Francis, Doublin; Norfadhilah, Ibrahim (Universiti Tun Hussien Onn Malaysia (UTHM), 2011)
International Conference on Building Science and Engineering (ICON-BSE 2009) organized by Universiti Tun Hussien Onn Malaysia (UTHM) from 14th - 15th December 2009 at Johor Bahru, Johor, Malaysia.